THE EFFECT OF DIGITAL MARKETING, BRAND IMAGE, AND BRAND TRUST ON CONSUMER PURCHASE INTEREST IN GOOD SUPPLY - Primadiansyah Ridha Novrizal; Damelina Basauli Tambunan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to determine the effect of digital marketing, brand image, and brand trust on consumer purchase intention with Good Supply as the object of study. The variables used in this study are digital marketing, brand image, and brand trust as independent variables, and purchase intention as the dependent variable. The method used is quantitative with multiple linear regression analysis approach. The sample used in this study used a non-probability sampling method with a purposive sampling technique and a sample of 150 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be interpreted that digital marketing influences the purchase intention of Good Supply consumers. Brand Image influences the purchase intention of Good Supply consumers. Brand Trust influences the purchase intention of Good Supply consumers.